Indole reduces the expression of virulence related genes in Vibrio splendidus pathogenic to sea cucumber Apostichopus japonicus. (October 2017) - Zhang, Shanshan; Zhang, Weiwei; Liu, Ningning; Song, Tongxiang; Liu, Huijie; Zhao, Xuelin; Xu, Wei; Li, Chenghua
Abstract: Indole is a metabolite of tryptophan that can be synthesized by various bacteria. In the present study, production of indole by Vibrio splendidus Vs was determined using Kovac's reagent, and m/z was further determined by HPLC-MS. Extracellular indole reached a maximum concentration of 160 μM, when OD600 of V . splendidus Vs was approximately 0.9. In addition, glucose could reduce indole level, and 1% (m/v) glucose could reduce the mRNA level of tnaA, the gene encoding tryptophanase, down to 0.2%. To investigate the effects of indole on the mRNA levels of virulence related genes of V . splendidus Vs, mRNA levels of vsm, vsh and ABC respectively related to protease activity, haemolytic activity and ABC transporter ATP-binding protein were determined. Exogenous indole supplemented at a concentration of 125 μΜ could respectively down regulate the mRNA level of vsm, vsh and ABC to 16%, 13% and 11%. Meanwhile, indole could alter the expressions of immune related gene in Apostichopus japonicus . When coelomocytes were co-cultured with exogenous indole at a concentration of 125 μΜ, the mRNA level of Ajp105 and AjLBP/BPI1, were up regulated by 1.6-fold and 2.1-fold, respectively. Combined all the results in our study suggested that indole could alter the expressions of the virulence related genes in pathogenic V. splendidus Vs as well as the immune related genes in A . japonicus . Highlights: Indole was detected in growth dependent and glucose inhibition patterns. Indole can inhibit the expressions of virulence related genes in V. splendidus. Indole can interfere the expressions of immune related genes in host.